WORK ENGAGEMENT DENGAN PERCEIVED ORGANIZATIONAL SUPPORT PADA KARYAWAN YANG MELAKUKAN WORK FROM HOME - Florentina Yuni Apsari; Vincentius Michael Wijaya (Universitas Katolik Widya Mandala Surabaya, 2022)
The COVID-19 pandemic has caused the work system that was originally in the office to now work from home or what we usually know as work from home (WFH). Work from home causes employee not to get full support from the company, such as the absence of work support facilities and having to provide work needs while work at home. These things make employee more lazy at work, feel their work is heavy, etc. decreased enthusiasm for wok is one aspect of work engagement. According to Schaufeli & Bakker (2004) work engagement is a condition of thinking about work where a person has positive thoughts and feels happy about work that is formed through vigor, dedication, and absorption. The factor that affect work engagement are perceived organizational support. Researchers use quantitative research method, researchers use google form as a medium for data collection. The number of subjects obtained by the researchers were 84 respondents (WFH employees). The results of this study show sig. of 0.000 (p <0.05) means that there is a relationship between work engagement and perceived organizational support for employees who do WFH. This study is supported by a correlation value of 0.391 and an effective contribution of 31.9% so that it can be said that the two variables studied have a positive relationship, which means that when individuals have high perceived organizational support, the individual will also have high work engagement. On the other hand, when an individual has low perceived organizational support, the individual will have low work engagement.